EFFECT SPRAY BY HUMIC ACID ON YIELD AND QUALITY OF POTATOES UNDER CONDITIONS OF AUTUMN CULTIVATION. - A. Juboori (Mesopotamia Journal of Agriculture)
The study was conducted at the Faculty of Agriculture and Forestry during the season autumn 2010, the experiment included two factors: two cultivars and spraying Humic acid and carried out according to RCBD. The results showed superiority of Santa cultivar on the Ltuna cultivar in most of the characteristics of vegetative growth and yield, while showed treatment of spraying Humic acid exceed the level of spraying 4.5 mil / liter in the characteristics of leaf area , yield per plant, tuber weight , tuber length , tuber diameter and marketable yield , but did not differ with level of spraying 3 mil / liter in the yield per plant and marketable yield , the interaction Santa cultivar under spraying 4.5 mil / liter recorded highest values in leaf area per plant, yield per plant , tuber weight , tuber length , tuber diameter, while superiority of santa cultivars under level of spraying 3 mil / liter on yield per plant and marketable yield, but did not different from Santa cultivar under the level of spraying 4.5mil / liter in that characteristics .